The Impact of Excellent Administrative Services on Student Satisfaction at State Islamic Senior High Schools - Syafira Aulia Putri; Irawati Irawati; Rini Setyaningsih (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the impact of excellent administrative services on student satisfaction at MAN 1 Pekanbaru. Using a quantitative approach with simple linear regression analysis, the study found that excellent administrative services contributed 74.1% to student satisfaction, as indicated by a coefficient of determination (R Square) of 0.741. The correlation test revealed a very strong and significant relationship between excellent administrative services and student satisfaction, with a correlation coefficient of 0.861 and a significance level of 0.000 (Sig. 2-tailed). These findings underscore the critical role of excellent services in improving student satisfaction, which also serves as an indicator of educational quality. Therefore, it is recommended that schools conduct regular monitoring and evaluation of their services to ensure sustained student satisfaction and continuous improvement in service quality.